Restricted expression of N- and R-cadherin on neurites of the developing chicken CNS - Redies, C (J Neurosci, 1992)
The expression of two cadherins, N- and R-cadherin, was mapped in the CNS of chicken embryos of 6–11 d incubation, focusing on the sensory and motor fiber systems. In the spinal cord, the laterally located fibers of the dorsal funiculus express N-cadherin while the medially located fibers do not. These two fiber systems have a different course within the CNS but associate to form the spinal dorsal roots. In the hindbrain, N-cadherin is expressed by the descending trigeminal (general somatic sensory) tract, which is contiguous with the N- cadherin-positive zone of the dorsal funiculus of the spinal cord. R- cadherin is not expressed by sensory fibers, but is expressed by the visceral motor system of the vagus and glossopharyngeal nerves, which are N-cadherin negative. The motor neurites expressing R-cadherin have a different course within the brain than the sensory neurites expressing N-cadherin, although they form the common sensory/motor roots of the vagus nerve at the surface of the brain. The possibility that N-cadherin provides a guidance cue for sensory axon migration within the CNS by a homophilic adhesion mechanism was investigated in vitro. Explants from sensory spinal ganglia expressing N-cadherin were placed on N-cadherin-transfected neuroblastoma cells, and axon outgrowth was visualized. Results showed that the sensory axons defasciculate and closely follow the cell-cell boundaries between transfected cells where high levels of N-cadherin are expressed. These results show that the two cadherins, like members of the immunoglobulin superfamily of molecules, are expressed in a topographically restricted fashion during chick brain development. They furthermore suggest that N- cadherin expression by neurites may play a role in guiding these neurites along CNS paths that express the same molecule.